Contribuição do estudo químico das raízes de Duguetia furfuracea (A. ST. -Hil.) Saff (Annonaceae) e atividade antibacteriana - Santos, Thiara Cruz Botelho (2018)
Duguetia furfuracea (Annonaceae) species popularly known as “sofre-dosrins-quem-quer”, can be found mainly in midwest, southeast and northeast regions. In folk medicine, tea from its leaves is indicated to combat dysmenorrhea and diarrhea. The bark and root teas are used for rheumatism, as soothing, stomachache, renal colic and backache. This work describes the isolation and identification of the special metabolites through the phytochemical study, as well as the evaluation of the antibacterial activity of the crude extract (EBHER) and fractions hexane (FH), dichloromethane (FD), ethyl acetate (FAcOet) and methanol (FMeOH) from the roots of D. furfuracea. Four substances were isolated, which were identified by 1H NMR spectroscopy, α-asarone, asaraldehyde, O-methylmoscatoline and staudine, the latter identified by 1H, 13C (1D and 2D), IR, and high resolution mass spectrometry ESI (+)-MS. The antibacterial assay was performed by the broth microdilution method through 96-well plates for the determination of the minimum inhibitory concentration (MIC) using the ATCC, Gram positive and Gram negative strains, and EBHER and FD showed moderate inhibitory activity (MIC = 500 μg / mL) and K. pneumoniae (MIC = 250 and 125 μg / mL, respectively). FHex was active against K. penumoniae (MIC = 500 μg / mL). The chemical study carried out with the roots of D. furfuracea identified that the phenylpropanoids α-asarone and asaraldehyde, already described in the literature, were found mainly in the apolar fractions. The alkaloids Omethylmoscatoline and staudine, through the present study, are being reported for the first time in this species, thus contributing to the amplification of the chemotaxonomic knowledge of this plant.